ความหลากชนิดของไบรโอไฟต์ในพื้นที่ชุ่มน้ำบึงสำนักใหญ่ จังหวัดระยอง - ฐายินี พลวงศ์ตระกูล (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Bryophytes are non-vascular plant that important role in the ecosystem consist of indicate humidity conditions, maintain moisture in the forest. From the literature review was found that the diversity and distribution of bryophytes were studied in many areas in Thailand but still lacking the study of this plants in the wetland which is an important ecosystem that is currently affected by human activities. The objective of this research is to study diversity and map distribution of bryophytes in Bueng Sam Nak Yai Wetland, Rayong Botanical Garden, Rayong Province. The specimens of bryophytes were collected from September 2018 to January 2019 in 6 routes of nature trails, record the geographic data of bryophytes via Google maps version 5.13.11. to map distribution of each bryophytes. All of the specimens were studied in morphological and anatomical characteristics to identify species. From enumerated 56 specimens, 10 families, 12 genera, 14 species including 12 species of mosses and 2 species of liverworts. The bryophytes were classified into 3 groups based on their habitats, including 7 terrestrials, 6 epiphytes and 1 lithophyte. The most of wide distribution species is Archidium birmannicum Mitt. ex Dixon and the least found are Leucobryum juniperoideum (Brid.) Müll. Hal. and Sematophyllum subhumile (Müll. Hal.) M. Fleisch. The results of this study will be forwarded to the Rayong Botanical Garden to prepare documents for publish. The specimens are deposited in the Professor Kasin Suvatabhandhu Herbarium, department of botany, faculty of science, Chulalongkorn University to be used as an academic reference.